2020
DOI: 10.1080/21655979.2020.1752594
|View full text |Cite
|
Sign up to set email alerts
|

Effect of organic compounds on dry anaerobic digestion of food and paper industry wastes

Abstract: Effects of antimicrobial compounds on dry anaerobic digestion (dry-AD) processes were investigated. Four compounds with known inhibition effects on traditional wet digestion, i.e. car-3-ene, hexanal, 1-octanol and phenol were selected and investigated at concentrations of 0.005%, 0.05% and 0.5%. Food waste (FW) and Paper waste (PW) were used as model substrates, all assays were running with the substrate to inoculum ratio of 1:1 (VS basis) corresponding to 15% TS in reactors. Generally, increasing concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, a complete inhibition was observed when the concentration was further increased to 5600 mg/L. In another study, Jansson et al [30] observed that methane yield was reduced by 66% when phenol concentration increased from 0.005 to 0.05 (w/v %) during the anaerobic digestion of paper waste.…”
Section: Influence Of Substrate Loadingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a complete inhibition was observed when the concentration was further increased to 5600 mg/L. In another study, Jansson et al [30] observed that methane yield was reduced by 66% when phenol concentration increased from 0.005 to 0.05 (w/v %) during the anaerobic digestion of paper waste.…”
Section: Influence Of Substrate Loadingmentioning
confidence: 99%
“…As discussed in Section 3.4.1, the concentration of inhibitory compounds at a certain level could be beneficial to the AD process. At the same time, the microbial community can also adapt to these inhibitory compounds up to a certain concentration [30]. However, the further rise in the same compounds could inhibit the process.…”
Section: Influence Of Substrate Loadingmentioning
confidence: 99%
“…The highest methane production reached 0.34 L g −1 VS added , co-digest of apple pulp, cow slurry, and olive pomace have produced stable biogas of 400 L/kg volatile solids. Jansson et al [ 23 ] investigated CSTR for digestion of residue of vegetables, the digestion of sugar beet pulp and asparagus waste led to a methane generation of 0.263 and 0.230 l g −1 VS fed, respectively, and reduction in VS equal to 95.2% and 89.7%. In comparison to single-phase digestion, batch sequencing reactors are becoming more critical for anaerobic digestion, when it comes to enhancing solid retention and unsettlement.…”
Section: Resource Recovery From Apple Orchard Wastementioning
confidence: 99%